Early child development in children who are HIV‐exposed uninfected compared to children who are HIV‐unexposed: observational sub‐study of a cluster‐randomized trial in rural Zimbabwe. Issue 5 (9th May 2020) - Ntozini, Robert; Chandna, Jaya; Evans, Ceri; Chasekwa, Bernard; Majo, Florence D; Kandawasvika, Gwendoline; Tavengwa, Naume V; Mutasa, Batsirai; Mutasa, Kuda; Moulton, Lawrence H; Humphrey, Jean H; Gladstone, Melissa J; et al.
Abstract: Introduction: Exposure to maternal HIV may affect early child development (ECD), although previous studies have reported heterogeneous findings. We evaluated ECD among children who were HIV‐exposed uninfected (CHEU) and children who were HIV‐unexposed (CHU) recruited to the SHINE trial in rural Zimbabwe. Methods: SHINE was a community‐based cluster‐randomized trial of improved infant feeding and/or improved water, sanitation and hygiene. Pregnant women were enrolled between 2012 and 2015. We assessed ECD in a sub‐study at 24 months of age, between 2016 and 2017, using the Malawi Developmental Assessment Tool (MDAT; assessing motor, cognitive, language and social development); MacArthur‐Bates Communicative Development Inventory (CDI) (assessing vocabulary and grammar); A‐not‐B test (assessing object permanence); and a self‐control task. Mothers and infants were tested longitudinally for HIV. We used generalized estimating equations to compare ECD scores between CHEU and CHU, accounting for the cluster‐randomized design. Primary results were adjusted for trial‐related factors that could affect measurement reliability of ECD: study nurse, age of child, calendar month of birth, sex and randomized arm. Results: A total of 205 CHEU and 1175 CHU were evaluated. Mean total MDAT score was 90.6 (SD 8.7) in CHEU compared to 92.4 (9.1) in CHU (adjusted mean difference −1.3, 95% CI: −2.3, −0.3), driven mostly by differences in gross motor (−0.5, 95% CI: −0.9, −0.2) and language scores (−0.6, 95% CI: −1.1, −0.1). There was evidence that fine motor scores were lower in CHEU (adjusted mean difference −0.4, 95% CI: −0.8, 0.0) but no evidence of a difference in social scores (0.1, 95% CI: −0.2, 0.4). Mean MacArthur‐Bates CDI vocabulary score was 57.9 (SD 19.2) in CHEU compared to 61.3 (18.8) in CHU (adjusted mean difference −2.9 words, 95% CI: −5.7, −0.1). Object permanence and self‐control scores were similar between groups. Conclusions: CHEU in rural Zimbabwe had total child development and vocabulary scores that were approximately 0.15 standard deviations lower than CHU at two years of age. More detailed and specific studies are now needed to unravel the reasons for developmental delay in CHEU and the likelihood that these delays persist in the longer term.